CHANGES IN THROMBOCYTOGRAM INDICATORS AGAINST THE BACKGROUND OF ANTIVIRUS THERAPY IN PATIENTS WITH LIVER CIRRHOSIS WITH HCV ETIOLOGY - Nuriddionova Nodira Fakhriddin kizi (PEDAGOGS, 2024)
Nearly 290000 patients with chronic hepatitis C die annually from the most severe complications of the disease. One of them is liver cirrhosis, which occurs in about 20% of patients chronically infected with the hepatitis C virus (HCV). Direct-acting antivirals (DAAs), which replaced interferon (IFN)-based regimens, significantly improved the prognosis of this group of patients, increasing HCV eradication rates and tolerability of therapy. Our study is the first to assess changes in patient profile, effectiveness, and safety in the HCV-infected cirrhotic population in the IFN-free era.